BENEFIT COST RATIO (BCR) ANALYSIS ON THE RECONSTRUCTION WITH HARDENED ROAD SHOULDER PROGRAM IN EAST JAVA PROVINCE - Ahmad Faathir; Ratna Handayani (Journal Innovation of Civil Engineering (JICE), 2021)
One of the main program of The East Java Province Government on the road sector is the capacity improvement through Road Reconstruction with Hardened Shoulder Project in the Strategic Corridor in the road province to accelerate the goods and people transport as a tools to support the public economic welfare. The benefit cost ratio analysis is carried out to evaluate how big the direct benefit which was obtained by the road users through this program. The research is conducted on the five main road which represent the urban and inter-urban area by comparing the two conditions, the base alternative (do nothing) and alternative (do something) to obtain the benefit influenced by the Road Reconstruction with Hardened Shoulder Project which fulfilling the economic feasibility criteria which is The Benefit Cost Ratio, Net Preset Value (NPV) and Internal Rate of Return (IRR).The Research shows that the first year benefit of the Road Reconstruction with Hardened Shoulder Project gives the Vehicle Operating Cost (VOC) saving by 4,86% and The Travel Time saving by 15,57%. The Benefit evaluation along 10 Years program is known from five roads which was studied only three had qualified to fulfill the feasibility criteria, B/C > 1, NPV> 1 dan Nilai IRR > r (discount rate 12 %) which was ranked based on the NPV/Capital value respectively Bts. Kab. Sumenep - Pantai Lumbang road by 5.425, Jajag - Simpang Lima Petahunan – Pasanggaran road by 1.429 and Kencong – Kasian road by 0.591.